The B-cell non-Hodgkin’s lymphoma: An enigma to diagnose - Iyer, Shruti (Indian Journal of Case Reports, 2024)
Non-Hodgkin’s lymphoma is a heterogeneous group of malignancies characterized by an abnormal clonal proliferation of T-cells, B-cells, or both. Sometimes, tuberculosis and lymphoma presentation can share common symptoms and features. In this case report, we present the case of a 28-year-old female patient who came with a chief complaint of swelling on the right side of the face for the past 6 months. Initially, it was not associated with pain but gradually developed severe pain over the region and reduced salivary flow. The patient was planned for surgery with a differential diagnosis of salivary gland pathology. Post-operatively, the histopathological report showed atypical cells which were diffusely positive for cluster of differentiation (CD)20. Focally positive for CD45 and CD3 which was positive in reactive T lymphocytes. Immunohistochemistry pattern favors the diagnosis of B-cell type NHL. Through this case report, we want to share our experience in treating an aggressive tumor that mimics salivary gland pathology.